Beam test calibration of the balloon-borne imaging calorimeter for the CREAM experiment - AHN H. S.; BAGLIESI M. G.; BIGONGIARI G.; GANEL O.; HAN J. H.; HYUN H. J.; KANG T. G.; KIM H. J.; KIM K. C.; KIM M. Y.; KIM S.; KIM Y. J.; et al. (World Scientific Publishing, 2005)
CREAM (Cosmic Ray Energetics and Mass) is a balloon experiment designed for direct spectral and composition measurements of cosmic rays over the elemental range from proton to iron over the energy scale of 1015 eV. The first flight will take place at the end of 2004 from Antarctica. The instrument includes a thin ionization calorimeter designed to operate in the range of energies from a few hundred GeV to 1 PeV providing imaging capability in the reconstruction of the e.m. showers originated from the interaction of primary nuclei in the carbon target. The calorimeter has been calibrated with electron and hadron beams at CERN.The calibration procedure and preliminary beam test results will be reported.